Organizational Commitment Is Not An Important Thing To Employees Performance - Ngatimun, Ngatimun; Hermanto, Hermanto; Elmas, Mohammad Syarif H (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2021)
Performance is a job target, this research aim to find the contribution or effect of competence and job satisfaction through organizational commitment to performance with a sample of 83 employees of PDAM Kota Probolinggo, using path analysis with multiple linear regression with the amos application, giving the results that: competence and job satisfaction are not significant effect on organizational commitment, thus organizational commitment is not able to mediate employee competence and job satisfaction on employee performance results, and job satisfaction also does not significantly affect performance, only employee competence has a significant effect on employee performance, Componnents that need attention are motives, systems supervision, system operational procedures, co-workers and satisfaction with salaries